ACCEPTABLE TECHNOLOGIES IN THE IMPROVEMENT OF THE FILLER AND MIXTURE CONTACT ZONE - M.D. Saparboyev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The scientists of our country and abroad pay the main attention to the composition and structure of the contact zone of the filler and the mixture and the properties between them when forming the properties of concrete. Concrete strength, frost resistance, waterproofing property, gas permeability, and many other properties directly depend on the characteristics of the contact zones of the mixture with the filler.